ChemInform Abstract: High Surface Area CeO2 Promoted Suzuki—Miyaura Cross‐Coupling of Arylboronic Acids and Aryl Iodides. Issue 26 (6th June 2013) - Mayer, Marilyn Graziano; Nador, Fabiana; Volpe, Maria Alicia; Radivo, Gabriel
Abstract The heterogeneous CeO2 efficiently promotes the title reaction in the absence of any other transition metal catalyst.